Plan estratégico de mercadeo para el Hotel Cataratas Eco-Resort - Aponte-Quirós, Félix; Quesada-Solis, Esteban; Rojas-Sánchez, Mario (Instituto Tecnológico de Costa Rica., 2006)
The future is uncertain and unknown, the world’s economy, the changes in the environment, the development of new technologies and the population's growth, among other factors, make the managerial future to be a challenge. In such a way the companies should take in consideration new goals and changes in the environment. The global focus the companies are exposed weakens them if they are not able to stay competitive itselves. That planning of the new century, makes them replant the future to a short, medium and a release term constantly, in a changing environment. Having plans, goals, politics and clear objectives, are components of the General Strategic Plan. The companies have to be able to visualize and build a proposal which involves profitability, responsibility, local culture and leadership. The investigation project has as objective to develop a strategic “plan of marketing for the Cataratas Eco-Resort Hotel”, located in The Fortuna of San Carlos. The hotel’s environment it’s analyzed and the impact of the tourist offer in the area. A very important factor was based on knowing the perception of the clients on the services received by the hotel and also the travel agencies that operate directly in the Fortune. To obtain the information two tools were used, which were executed, the first one by means of an applied survey at the travel agencies and the second an evaluation directly to the hotel, assuming the position of an incognito client. Once the information was processed and analyzed, it was possible to determine factors that impact directly in the general operation of the hotel, of elements that have helped to the growth and development of the same one and of critical factors that have generated problems. Therefore, the plan of strategic marketing is looking for an establishment on the stocks to continue and support to the general strategic position for the holding and growth of the same one. At this moment, the Cataratas Eco-Resort Hotel is in a reorganization process, so much for the definition of objectives to medium and a release term, as of decisive stocks in the short term. The proposal of the study has a strategic character, the operative stocks were not developed, and it will be responsibility of the hotel to take them to the practice.
Proyecto de graduación (Maestría en Administración de Empresas con Enfasis en Mercadeo) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2006.
Keywords: Planeación estratégica; Estrategia; Análisis administrativo; Mercadeo; Administración de empresas; Hoteles; Agencias de viajes